Competitiveness vis-à-vis service quality as drivers of customer loyalty mediated by perceptions of regulation and stability in steady and volatile markets. (May 2017) - Baumann, Chris; Hoadley, Susan; Hamin, Hamin; Nugraha, Albert
Abstract: The purpose of this research is to investigate predictors of customer loyalty in order to identify alternatives to customer satisfaction with service quality, which has been traditionally accepted as the primary predictor of customer loyalty, particularly for services. A stratified sample of bank customers was surveyed to collect information on customer perceptions and behaviors in relation to satisfaction with service quality, competitiveness, risk, regulation, stability and loyalty. Partial least squares path modelling (PLSPM) was applied to develop loyalty models for a steady market (Australia) and a volatile market (Greece). This study's empirical findings support theoretical arguments for the inclusion of customer perceptions of competitiveness in loyalty modelling. Perceptions of regulation and stability intervene in the relationship between drivers of loyalty and loyalty itself. For bankers, the study emphasizes the need to move away from customer satisfaction with service quality to explain customer loyalty, towards focusing efforts on achieving relative superiority in competitiveness, namely competitive productivity and products. Profiling customers based on their perceptions of a bank's competitiveness can provide additional explanatory power beyond traditional satisfaction based loyalty models. Services marketing has focused on the service components, and there is no doubt about its crucial role. But given this focus, other factors, such as the actual product component, have been somewhat overlooked in services research. The study makes a unique contribution to understanding and modelling customer loyalty by demonstrating the importance of the inclusion of customer perceptions of other factors as appropriate to market conditions.